Analysis Of The Influence Of Minimum Wages, Central-Regional Transfer Cost Allocation And Fiscal Decentralization On Regional Income Inequality - Indra Ismayudi Tanjung; Rahmat Al Hidayat; Sugeng Karyadi; Lalang Saksono; Odih Sumirat (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2024)
In any nation, income disparity is a crucial issue for development. The disparity in income distribution is the primary cause of income inequality. The increasing income disparity is a sign of the growing inequality in the allocation of income in society. The authors of this study aim to investigate how income inequality is affected in the regencies and cities of one of provinces minimum wage in Indonesia, central-local transfer cost allocation, and fiscal decentralization. The Fixed Effect Model (FEM) approach is used in this study's panel data analysis. The author's analysis indicates that while there is no significant association between income inequality and fiscal decentralization, there is a substantial relationship between income inequality and the allocation of central-regional transfer costs and the minimum wage. Income inequality is significantly impacted by fiscal decentralization, minimum wage, and central-regional transfer cost allocation.